Locus of Control, Leader Behavior and Leader Performance Among Management Students - Anderson, Carl R.; Schneier, Craig Eric (Academy of Management Journal, 1978)
This paper examines the relationships among internal-external (IE) locus of control, behaviors characteristic of internal versus external personality types, and leader and group performance. Results indicated that leaders were more likely to be internals than externals. Superior performance was achieved by internal leaders and by groups led by internals. A two-group stepwise discriminant analysis isolated 10 behaviors which maximally separated internals from externals. Internals exhibited behaviors characteristic of an instrumental, task-oriented style, and externals exhibited behaviors pointing to a social-emotional style. Implications for leadership theory and suggestions for future research are discussed.